Comparative Study of the CSR Intiatives of Microsoft, IBM, Google, Sun Microsystems & Cisco Systems in the Gulf Region - Ghazinoori, Seyed Amirhossein (2008)
As an integral part of our MBA course, we had to attend the final 60 credits of the course which was based on the dissertation. On the other side another option also suggested by the university and that was participating in managerial report related to one organization which was possible to attend as an individual and also it was possible to approach the project as a group and after that each member write the individual report based on his/her participation and contribution to the group report which is the basic idea of this paper. Totally the idea for us behind the participation in this project was improving our practical skills through working within group and feeling the group dynamics and policies more than before and beside of that, unique topic of the project and the brand of Microsoft as a multinational organization who suggested this topic to us, was the motivating factor for all of us including me to accept the project and report. Before that, I decided to do my dissertation in the field of strategic management and corporate strategy and in this direction the area which attracted me was brand management and role of CSR (Corporate Social Responsibility) in between. But by suggestion of the managerial report from Huzaifa Sikander (One of the group members) and related discussions which I will mention later, my decision turned into the managerial report in the field of CSR instead of dissertation in this area which was more practical instead of theoretical. Basically group report that we decided to attend and prepare, suggested by Microsoft Corporation Gulf region. And totally the whole idea and topic which managers at Microsoft were enthusiastic to offer us was comparison study of the CSR initiatives of ICT firms in the Gulf region and they specifically mentioned to particular Microsofts competitors and vendors in this region which were IBM, Cisco Systems, Google and Sun Microsystems.